Phylogenetic studies of magnoliids: Advances and perspectives - Shen, Zhiguo; Ding, Xin; Cheng, Jianming; Wu, Fangfang; Yin, Hengfu; Wang, Minyan (Frontiers in Plant Science, 2023)
Magnoliids are the largest flowering plant clades outside eudicots and monocots, which are distributed all over the world and have high economic and ornamental value. Eudicots, monocots and magnoliids are the three major clades of mesangiospermae, and their phylogenetic relationship is one of the most interesting issues. In recent years, with the continuous accumulation of genomic information, the evolutionary status of magnoliids has become a hot spot in plant phylogenetic research. Although great efforts have been made to study the evolution of magnoliids by using molecular data such as nuclear genome, plastid genome, mitochondrial genome, transcriptome, and other molecular data of several representative species, the current results of the study on the phylogenetic status of magnoliids are not consistent. Here, we systematically describes the current understanding of the molecular research on magnoliids phylogeny, and reviews the differences in the evolutionary state of magnoliids. Understanding the research approaches and limitations of magnoliids phylogeny can guide the research strategies to further improve the study on the phylogenetic evolution of magnoliids.